QUALITY EVALUATION OF ORGANIC DAIRY PRODUCTS IN RELATION TO THE CONVENTIONAL - Maria NICA; Ionut Laurentiu PETRE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this paper proposes assessment of the quality of milk products from two perspectives, conventional and organic products. In the first part of the paper, by studying literature, will bring attention to their views about the relationship between prejudice and conventional and organic products in terms of quality and price. The main research methods used throughout the paper method will be: SAIN-LIM, with which it will be able to appreciate the level of quality of such products and the method of comparative analysis of the results obtained after calculating the two indicators. In the second part will choose a product ecological and conventional for several categories of dairy products to determine the value of the indicators described above. Thus, with the help of these results can appreciate differences in terms of the quality of certain conventional and ecological products and their impact on population health.